An optimal control method for discrete variable outdoor air volume setpoint determination in variable air volume systems. (January 2020) - Zhao, Tianyi; Hua, Pengmin; Dai, Wuhe; Zhang, Jili; Ma, Liangdong
Abstract: In multi-zone variable outdoor air (OA) volume air-conditioning systems, there is often a mismatch between OA volume flow supply and demand, because variable air volume (VAV) systems exhibit nonlinear, multivariable, and long delay characteristics. Traditional methods ensure indoor air quality (IAQ) by increasing OA volume flow, which leads to a waste of OA flow energy. To address this problem, an optimal control method for determining discrete variable OA volume flow setpoints, based on differential pressure control, is proposed in this study. In this method, changes in indoor CO2 concentration and the total air volume flow demand of terminals are regarded as constraints of OA volume flow setpoints. A Proportional-Integral (PI) calculation method and trial-and-error method are used to discretize continuous OA volume flow setpoints to increase system stability. Two types of experiments were conducted to compare the characteristics of the two discrete OA volume flow setpoint determining methods, and to verify the feasibility of our new approach. The results show that the OA volume flow control loop can be well fitted with other control loops of VAV systems, and ensure OA volume flow demand for a target area. The proposed method provides greater energy savings than maximum OA ratio control strategy (7%–22%) and typical on-demand ventilation method (6.1%), and better control performance than continuous OA volume flow setpoints control system. The PI calculation method is suitable for conditions with high IAQ requirements, while the trial-and-error method can be used for comfort air-conditioning systems to adjust the indoor environment. Highlights: An optimal control method for outdoor volume flow in variable air volume system is proposed. Two methods are used to discretize continuous outdoor air volume setpoint. The proposed method provides greater energy savings than typical control strategies. The proposed method provides better control performance than continuous outdoor air volume flow setpoints control system. The proposed method is easy to implement and duplicate in most outdoor volume control system.